Brand Equity and Brand Trust on Purchasing Decisions Somethinc Products with E-WOM as Intervening Variable (Case Study: Djuanda University 2023/2024 Students) - Fatya Permata Ambyya Sukmedi; Palahudin; Rachmat Gunawan (MultiTech Publisher, 2025)
This research aims to analyze the influence of brand equity and brand trust on purchasing decisions with electronic word of mouth (E-WOM) as an intervening variable. The study involved a population of 514 individuals, with a sample of 100 respondents selected using a quota sampling technique. Data were collected through interviews, questionnaire distribution, and observations. The data analysis was conducted using path analysis with the assistance of SPSS version 27.00. The findings indicate that brand equity and brand trust positively and significantly impact E-WOM. Furthermore, brand equity, brand trust, and E-WOM positively and significantly influence purchasing decisions. Additionally, brand equity and brand trust indirectly affect purchasing decisions through E-WOM.